Power and proliferation: Explaining the fragmentation of global migration governance. (13th August 2020) - Kainz, Lena; Betts, Alexander
Abstract: Fragmentation is widely recognised as one of the defining characteristics of global migration governance. However, there has been little academic analysis of fragmentation, either as a dependent or independent variable in the international politics of migration. We aim to explain why it is that global migration governance has historically emerged as a patchwork of international institutions. In order to do so, we outline an original theoretical framework based on the proposition that power asymmetries between predominantly 'sending' and 'receiving' countries create a dynamic in which relatively weak states seek multilateralism and relatively strong states veto multilateralism, leading to institutional proliferation as a means to address immediate functional challenges. We apply this framework to four key historical turning points in the recent history of global migration governance: first, the impasse at the United Nations and the expansion of Regional Consultative Processes (1985–2001); second, the surge of new mandate creations and the first High-Level Dialogue on Migration and Development (1999–2006); third, the establishment of the Global Forum on Migration and Development and the Global Migration Group (2006–8); and finally, the New York Declaration and the Global Compact for Safe, Orderly and Regular Migration (2016–18).